Depressive Symptoms and Quality of Life in Patients With Heart Failure and an Implantable Cardioverter-Defibrillator - Zormpas, Christos; Kahl, Kai G.; Hohmann, Stephan; Oswald, Hanno; Stiel, Christopher; Veltmann, Christian; Bauersachs, Johann; Duncker, David (Frontiers in Psychiatry, 2022)
Background: Heart failure (HF) is associated with development of depressive symptoms and reduced quality of life (QoL). Patients with HF and an implantable cardioverter-defibrillator (ICD) were evaluated regarding depressive symptoms and QoL. Methods: The present study included 446 patients with HF and an ICD. Depressive symptoms were assessed using the Patient Health Questionnaire 9 (PHQ-9), QoL was evaluated using the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Functional ability and exercise tolerance were assessed at inclusion and after 6 months with help of the 6-minute walking test (6MWT). Results: Patients included in the study had a mean age of 65.8 years and were predominantly male (83.6%), with mostly ischemic (n = 277; 62.1%) or dilated (n = 150; 33.6%) cardiomyopathy. 193 (43.2%) patients had depressive symptoms, of whom 75 patients (16.8%) were classified as moderate to severe depression according to the PHQ-9 at baseline. Depressive symptoms were associated with low QoL independent of NYHA functional class. High NYHA functional class, high PHQ-9 score, age and body mass index (BMI) were associated with a lower 6MWT at enrollment, while depressive symptoms (expressed as higher PHQ-9 score) and age were associated with a lower 6MWT after 6 months. Patients with history of smoking and a higher BMI showed higher PHQ-9 scores after 6 months. Patients under antidepressant medication showed improved PHQ-9 score after 6 months, indicating controlled/treated depression. However, patients with low QoL at inclusion remained with low QoL after 6 months. Conclusion: Depressive symptoms correlate with low QoL and lower long-term functional status in patients with HF and an ICD. Depressive symptoms are associated with smoking and obesity, which themselves are risk factors for a poor prognosis in HF. Only a small fraction of patients with HF and ICD showing depressive symptoms receives appropriate treatment. Assessing depressive symptoms and lifestyle factors should be part of a multimodal treatment plan in patients with HF and an ICD.